2020
DOI: 10.3390/brainsci10020079
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Electrophysiological Correlates of Performance Monitoring and Development in Children and Adolescents with Attention-Deficit/Hyperactivity Disorder

Abstract: The pathophysiology of attention-deficit/hyperactivity disorder (ADHD) involves deficits in performance monitoring and adaptive adjustments. Yet, the developmental trajectory and underlying neural correlates of performance monitoring deficits in youth with ADHD remain poorly understood. To address the gap, this study recruited 77 children and adolescents with ADHD and 77 age- and gender-matched healthy controls (HC), ages 8–18 years, who performed an arrow flanker task during electroencephalogram recording. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…It involves participants being instructed to identify a target stimulus defined by its directionality (i.e., the directionality of an arrow) while ignoring other distracting stimuli that flanking the target stimulus. In general, children with ADHD display longer RT (Liu et al, 2020) and lower response accuracy (Johnstone and Galletta, 2013) compared with typically developing children during the flanker task.…”
Section: Introductionmentioning
confidence: 94%
“…It involves participants being instructed to identify a target stimulus defined by its directionality (i.e., the directionality of an arrow) while ignoring other distracting stimuli that flanking the target stimulus. In general, children with ADHD display longer RT (Liu et al, 2020) and lower response accuracy (Johnstone and Galletta, 2013) compared with typically developing children during the flanker task.…”
Section: Introductionmentioning
confidence: 94%
“…They did find, as did Jonkman et al ( 1999 ), that error rate, not response speed, distinguished the two groups; the increase in error rate for incongruent relative to neutral arrays was larger among children diagnosed with AD/HD than among controls. FMRI analyses suggested that this differential increase in error rate may be associated with a differentially larger reduction of activation in neural pathways that mediate response inhibition (in particular, the caudate nucleus) compared with those that mediate interference suppression among children diagnosed with AD/HD (for related findings, see Liu et al 2020 ; Plessen et al, 2016 , discussed below).…”
Section: Arrow Flankers and Online Action Control In Developmental Anmentioning
confidence: 99%
“…They found, as had the bulk of the studies reviewed above, that the reduction in response speed and accuracy induced by incongruent arrays was comparable between the two groups. Most recently, Liu et al ( 2020 ) examined the processing of arrow flankers in a relatively large sample of children and adolescents with AD/HD. Responses were slower and less accurate to incongruent than to congruent arrays, and the congruence effect on the speed of responding was, at trend-level significance, more pronounced in participants with AD/HD compared with controls.…”
Section: Arrow Flankers and Online Action Control In Developmental Anmentioning
confidence: 99%
“…The frontal N2 is thought to be specifically related to conflict detection when facing two competing stimuli (e.g., task-relevant vs. task-irrelevant information) 15 . Evidence has indicated that children with ADHD have smaller N2 amplitude during inhibitory control tasks when compared to their typically developing (TD) counterparts, which may imply failures in conflict detection 16 , 17 . Despite a paucity of research delineating the modulatory effects of acute exercise on the N2 in children with ADHD, findings from other clinical population with deficits in inhibitory control could provide hints regarding the potential effects of acute exercise.…”
Section: Introductionmentioning
confidence: 99%